Deliberative democracy - Elster, Jon 1940- (Cambridge, [England] Cambridge University Press, 1998)
It is sometimes assumed that voting is the central mechanism for political decision making. However, the contributors to this volume focus on an alternative mechanismdecision by discussion or deliberation. These original contributions include case studies based on historical and current instances of deliberative democracy, normative discussion of the merits of deliberation compared with other models of collective decision making, and studies of the conditions under which deliberation tends to improve the quality of decisions. This volume takes a realistic approach: rather than assuming that deliberative democracy is always ideal, the authors critically probe its limits and weaknesses as well as its strengths. --Publisher description.
"Claro!" : an essay on discursive machismo / Diego Gambetta -- Deliberation as discussion / James D. Fearon -- All men are liars : is democracy meaningless? / Gerry Mackie -- Deliberation and constitution making / Jon Elster -- Pathologies of deliberation / Susan C. Stokes -- Deliberation and ideological domination / Adam Przeworski -- Arguing for deliberation : some skeptical considerations / James Johnson -- Democracy and liberty / Joshua Cohen -- Health-health trade-offs / Cass R. Sunstein -- Full representation, deliberation, and impartiality / Roberto Gargarella.
Reprinted 1999.
Includes bibliographical references and index.
Keywords: Deliberative democracy; Decision making; Representative government and representation; Democracy